Targeting host-derived glycans on enveloped viruses for antibody-based vaccine design - Crispin, Max (Curr Opin Virol, 2015)
The surface of enveloped viruses can be extensively glycosylated. Unlike the glycans coating pathogens such as bacteria and fungi, glycans on viruses are added and processed by the host-cell during biosynthesis. Glycoproteins are typically subjected to α-mannosidase processing and Golgi-mediated glycosyltransferase extension to form complex-type glycans. In envelope viruses, exceptions to this default pathway are common and lead to the presence of oligomannose-type glycan structures on the virion surface. In one extreme example, HIV-1 utilizes a high density of glycans to limit host antibody recognition of protein. However, the high density limits glycan processing and the resulting oligomannose structures can be recognised by broadly neutralising antibodies isolated form HIV-1 infected patients. Here we discuss how divergence from host-cell glycosylation can be targeted for vaccine design.